Health promotion activities of sports clubs and coaches, and health and health behaviours in youth participating in sports clubs: the Health Promoting Sports Club study - Kokko Sami; Selänne Harri; Alanko Lauri; Heinonen Olli J; Korpelainen Raija; Savonen Kai; Vasankari Tommi; Kannas Lasse; Kujala Urho M; Aira Tuula; Villberg Jari; Parkkari Jari (BMJ Publishing Group, 2022)
Introduction: Sports clubs form a potential setting for health promotion, but the research is limited. The aim of the Health Promoting Sports Club (HPSC) study was to elucidate the current health promotion activities of youth sports clubs and coaches, and to investigate the health behaviours and health status of youth participating in sports clubs compared to non-participants.
Methods and analysis: The study design employs cross-sectional multilevel and multimethod research with aspirations to a prospective cohort study in the next phase. The setting-based variables at sports clubs and coaching levels, and health behaviour variables at the individual level, are investigated using surveys; and total levels of physical activity are assessed using objective accelerometer measurements. Health status variables will be measured by preparticipation screening. The health promotion activity of sports clubs (n=154) is evaluated by club officials (n=313) and coaches (n=281). Coaches and young athletes aged 14-16 (n=759) years evaluate the coaches' health promotion activity. The survey of the adolescents' health behaviours consist of two data sets-the first is on their health behaviours and the second is on musculoskeletal complaints and injuries. Data are collected via sports clubs (759 participants) and schools 1650 (665 participants and 983 non-participants). 591 (418 athletes and 173 non-athletes) youth, have already participated in preparticipation screening. Screening consists of detailed personal medical history, electrocardiography, flow-volume spirometry, basic laboratory analyses and health status screening, including posture, muscle balance, and static and dynamic postural control tests, conducted by sports and exercise medicine specialists.
Ethics and dissemination: The HPSC study is carried out conforming with the declaration of Helsinki. Ethical approval was received from the Ethics Committee of Health Care District of Central Finland. The HPSC study is close-to-practice, which generates foundations for development work within youth sports clubs.